2004
DOI: 10.1579/0044-7447-33.6.324
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Background Nutrient Concentrations in Coastal Waters: A Case Study from an Urban Embayment of the Baltic Sea

Abstract: Successful management of damaged coastal ecosystems requires reliable scientific evidence of their past state. Here we demonstrate that the sediment record of biotic indicators can be used to quantitatively reconstruct nutrient concentrations preceding the short time span covered by monitoring records. We generated a diatom-based weighted-averaging partial least squares transfer function model for total dissolved nitrogen with a prediction accuracy of 0.09 microg L(-1) (log10 units). The model was applied to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…However, some inference models have been developed and applied (e.g. Juggins 1992;Gehrels et al 2006;Ryves et al 2004;Ellegaard et al 2006;Horton et al 2006;Weckström et al 2004;Hassan et al 2009). In Australia, diatom inference models for coastal lake and estuarine environments have so far been developed for relatively small geographic regions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, some inference models have been developed and applied (e.g. Juggins 1992;Gehrels et al 2006;Ryves et al 2004;Ellegaard et al 2006;Horton et al 2006;Weckström et al 2004;Hassan et al 2009). In Australia, diatom inference models for coastal lake and estuarine environments have so far been developed for relatively small geographic regions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recorded commonly in sediments surrounding the Vistula River Mouth (Witkowski 1994, Witkowski & Pempkowiak 1995, Stachura & Witkowski 1997, Stachura-Suchoples 1999, this halophilous taxon proved to be an indicator of the influence by riverine waters (Leśniewska & Witak 2008). This diatom was also observed in samples from the Szczecin Lagoon (Andrén 1999, Bąk et al 2001, Bąk 2004, the Gulf of Finland (Weckström et al 2004, Clarke et al 2006 and the Roskilde Fjord (Clarke et al 2003(Clarke et al , 2006.…”
Section: Discussionmentioning
confidence: 83%
“…In the study area it was observed by Witkowski (1994), Witkowski & Pempkowiak (1995), Stachura & Witkowski (1997), Stachura (1999), Witak (2000), , Leśniewska & Witak (2008) and Witak (2010). This species was recorded also in the Gulf of Finland (Weckström et al 2004, Clarke et al 2006) and the Gulf of Riga (Olli et al 2008) and the Szczecin Lagoon (Bąk et al 2001). Another species representing the same genus is C. meneghiniana.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations